2020
DOI: 10.1093/jxb/eraa344
|View full text |Cite
|
Sign up to set email alerts
|

The HD-ZIP IV transcription factor Tril regulates fruit spine density through gene dosage effects in cucumber

Abstract: Trichomes and fruit spines are important traits that directly affect the appearance quality and commercial value of cucumber. Tril (Trichome-less), an HD-Zip IV transcription factor, plays a crucial role in the initiation of trichomes and fruit spines, but little is known about their exact regulatory mechanisms. In this study, tissue expression pattern analysis indicated that Tril is expressed and functions in the early stage of organ initiation and development. Expression of the Tril gene under the control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…HDZIP transcription factors play key roles in trichome development. AtGL2 in Arabidopsis ( Szymanski et al, 1998 ), SIWo in tomato ( Yang et al, 2011 ), AaHD1 and AaHD8 in A. annua ( Yan et al, 2017 , 2018 ), and CsTril in cucumber ( Du et al, 2020 ) are HDZIP transcription factors that modulate trichome development.…”
Section: Phytohormones Are Important Regulators Of Trichome Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…HDZIP transcription factors play key roles in trichome development. AtGL2 in Arabidopsis ( Szymanski et al, 1998 ), SIWo in tomato ( Yang et al, 2011 ), AaHD1 and AaHD8 in A. annua ( Yan et al, 2017 , 2018 ), and CsTril in cucumber ( Du et al, 2020 ) are HDZIP transcription factors that modulate trichome development.…”
Section: Phytohormones Are Important Regulators Of Trichome Developmentmentioning
confidence: 99%
“…The GLABRA 1 (GL1)-GLABRA 3 (GL3)/ENHANCER OF GLABRA 3 (EGL3)-TRANSPARENT TESTA GLABRA 1 (TTG1) trichome development complex has been well studied ( Zhao et al, 2008 ); however, knowledge of the interaction between this complex and phytohormones is limited. Sweet wormwood ( Artemisia annua ), tomato ( Solanum lycopersicum ), and cucumber ( Cucumis sativus ) are the main plant species used as models for studying glandular trichome development ( Lv et al, 2017 ; Du et al, 2020 ; Xiong et al, 2020 ), and many studies have indicated that trichome development involves phytohormones ( Yan et al, 2017 ; Chen et al, 2020 ; Yuan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different with mict-L130F mutants, in F 1 progeny, there only single copy of mict-L130F and the expression level of the gene may be affected. It has been reported that Tril has a gene dosage effect on fruit spine density [35]. Thus, we speculated that whether there is also a gene dosage effect existing in Mict and further research are needed.…”
Section: Discussionmentioning
confidence: 90%
“…Quantitative PCR (qPCR) was conducted using FastStart Universal SYBR Green Master Mix (ROX) (Roche) with a CFX96 Touch™ Real-Time PCR System. The cucumber CsActin gene was selected as an internal control [35]. Three biological replicates were used per gene.…”
Section: Sample Collection and Qrt-pcrmentioning
confidence: 99%
“…The mutation of the HD-ZIP IV transcription factor gene Tril (CsaV3_6G049180) could induce the occurrence of two other glabrous mutants (csgl3, tril) in cucumber [23,28,29]. Transgenic expression of the Tril gene could partly rescue the mutant phenotypes of tril, csgl3 and fs1 (few spines 1) [30]. The transformation of the TTG1 gene (Csa4Gm097650, WD-Repeat protein), the GA20ox1 gene (CsaV3_5G005560, gibberellin oxidase), the CsMYB6 gene (Csa009688, MYB transcription factor) and the CsTRY (Csa015371) gene in cucumber showed that all these genes could affect the development of trichomes [25,31,32].…”
Section: Introductionmentioning
confidence: 99%